2020
DOI: 10.3349/ymj.2020.61.5.391
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of Inflammatory Cytokine Genes and Risk for Intracranial Aneurysm: A Systematic Review and Meta-Analysis

Abstract: Purpose: Inflammatory cytokines are thought to be involved in the pathogenesis of intracranial aneurysm (IA), although results among studies in the literature are inconsistent. This article sought to review studies on the associations among polymorphisms in inflammatory cytokine genes and IA risk and to provide recommendations for future research. Materials and Methods: A systematic search of PubMed, Embase, and Web of Science was conducted up to August 4, 2019. The associations between polymorphisms of inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 41 publications
2
6
1
Order By: Relevance
“…Our result was supported by a previous MR study which showed sIL6R and CRP levels were not associated with IA [ 8 ]. Our finding was partially contradictory to a meta-analysis, which found no evidence of IL-1α, IL-1β, IL-6, and IL-12β against IA, but identified significant association of TNF-α polymorphism with IA [ 51 ]. Still, current epidemiological and experimental evidence for the role of inflammatory biomarkers in the formation and progression of IA remained insufficient, and thereby required future research to unveil the mystery.…”
Section: Discussioncontrasting
confidence: 99%
“…Our result was supported by a previous MR study which showed sIL6R and CRP levels were not associated with IA [ 8 ]. Our finding was partially contradictory to a meta-analysis, which found no evidence of IL-1α, IL-1β, IL-6, and IL-12β against IA, but identified significant association of TNF-α polymorphism with IA [ 51 ]. Still, current epidemiological and experimental evidence for the role of inflammatory biomarkers in the formation and progression of IA remained insufficient, and thereby required future research to unveil the mystery.…”
Section: Discussioncontrasting
confidence: 99%
“…A meta-analysis showed that two IL6 promoter polymorphisms (−174G/C and −572G/C) were associated with IA (Zheng et al, 2013). However, another recently published meta-analysis failed to confirm this association (Hu et al, 2020). Furthermore, a case-control study showed that levels of C-reactive protein (CRP), which is a well-established downstream molecule of IL6 signaling, were higher in patients with fusiform IA than controls (Mota Telles et al, 2020).With the increasing availability of summary data from genome-wide association studies (GWASs), new methods such as two-sample Mendelian randomization (MR) and linkage disequilibrium score (LDSC) regression have been widely used to determine the relationship between traits.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic databases including PubMed, Embase, and Web of Science were used for articles that had been published up to August 2022. The following key words were determined by referring to previous articles and used in “and” combinations [ 16 ] : “intracranial aneurysm(s)” or “cerebral aneurysm(s)” or “subarachnoid hemorrhage”, “inflammation” or “inflammatory cytokine” or “interleukin” or “tumor necrosis factor” or “high mobility group box 1” or “genetic” ( Fig. 1 and Supplementary Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Clinical information (e.g., authors, year, ethnicity, age, gender, and sample size) and genetic information (e.g., gene, SNP, and allele frequency) were collected. The quality of enrolled studies was evaluated using the Newcastle-Ottawa quality assessment scale [ 16 ]. The fixed-effect model assumes that one true effect size underlies all studies in the meta-analysis having a less heterogeneity between studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation